2007
DOI: 10.1259/dmfr/79378783
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery calcification seen on panoramic dental radiographs in the Asian population in Japan

Abstract: CAC may be seen on panoramic dental radiographs and is related to the patients' general history of CI, and the risk factors of CI in the Asian population in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 22 publications
5
26
0
3
Order By: Relevance
“…In the international literature, depending on the study, prevalence of carotid calcification in PRs were found to be between 0.4 and 4.0% [5,31-37]. The large range of values given for prevalence of positive findings of carotid calcification in PRs could be explained by the different age groups, different distributions of gender, ethnicity and lifestyles of the particular patients investigated [5].…”
Section: Discussionmentioning
confidence: 99%
“…In the international literature, depending on the study, prevalence of carotid calcification in PRs were found to be between 0.4 and 4.0% [5,31-37]. The large range of values given for prevalence of positive findings of carotid calcification in PRs could be explained by the different age groups, different distributions of gender, ethnicity and lifestyles of the particular patients investigated [5].…”
Section: Discussionmentioning
confidence: 99%
“…Doppler sonography of the carotid arteries is a routine measure of stroke risk. Carotid artery calcification can be seen on panoramic dental radiographs and can be related to a history of cerebral infarction (Kumagai et al 2007). Studies have demonstrated that the accuracy of panoramic radiographs against current gold standard for the diagnosis of carotid coronary calcification (doppler sonography) is high (Ravon et al 2003).…”
Section: Periodontitis‐cardiovascular Diseases – Association Studiesmentioning
confidence: 99%
“…A routine dental panoramic radiograph has been reported to be able to depict calcified carotid atheromatous plaques [7,15,16]. A calcified plaque appears as either a nodular radiopacity or a verticolinear radiopacity inferior to the mandibular angle, and adjacent to the cervical vertebrae at the level of the C3-C4 intervertebral junction [17][18][19].…”
Section: Introductionmentioning
confidence: 99%